ANALYSIS OF RED BLOOD CELL DISTRIBUTION WIDTH VALUE TOWARDS FIBROTIC STAGE IN CHRONIC HEPATITIS B - Fatma Idris; Darwati Muhadi; Mutmainah Mutmainah (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Chronic hepatitis-B is a liver disease caused by hepatitis B virus infection lasting for more than 6 months since the first appearance of signs and symptoms. Red Blood Cell Distribution Width (RDW) is more related to an inflammation process compared to the fibrotic stage. Increase in RDW value results from an increase in erythrocyte destruction or ineffective erythrocyte production caused by the inflammation process. The inflammation can suppress erythrocyte maturation and enable new reticulocytes to be released into blood circulation. Liver inflammation is the characteristic of chronic hepatitis B virus infection. This study aimed to know the RDW value towards the fibrotic stage in chronic hepatitis B patients. This study was a retrospective study conducted in the Dr. Wahidin Sudirohusodo Hospital Makassar. The data were taken from medical records of chronic hepatitis B patients in January 2015-July 2016. The research subjects were chronic hepatitis B patients who underwent routine blood examination for the first time when the patients had just hospitalized. The investigated was continued with fibroscan examination in Gastroenterohepathology Department of the Dr. Wahidin Sudirohusodo General Hospital. Statistical analysis was analyzed with Kruskal-Wallis test using SPSS ver.22. One hundred data of chronic hepatitis B patient consisted of 27 patients without fibrosis, 16 with moderate fibrosis and 11 with severe fibrosis were obtained in this study. Kruskal-Wallis test results showed no significant difference between RDW value with a fibrotic stage in chronic hepatitis B patient (p = 0.255). This study results showed no significant difference between RDW value and fibrotic stage in chronic hepatitis B patients. Red blood cell distribution width value cannot be used as a predictor of liver fibrosis. It is suggested to conduct further studies using larger sample size and more equally distributed sample based on fibrotic stage.